Youth unemployment in resource-rich Sub-Saharan Africa: A critical review. Issue 1 (January 2016) - Ackah-Baidoo, Patricia
Abstract: This paper critically reviews the youth unemployment crisis in resource-rich Sub-Saharan Africa. Although the region has experienced continuous and a seemingly limitless flow of investment in all types of extractive industries in recent decades, this growth has not directly translated into significant poverty reduction. Its overdependence on natural resources economically seems to have had a negative impact on socioeconomic development overall, generating very few jobs for youth and exacerbating existing unemployment crises. The paper uses Ghana, one the region's top mineral-rich countries, as a case study to explore these issues further.